KAJIAN TENTANG PENDETEKSIAN SEL DARAH PUTIH PADA CITRA PREPARAT DENGAN METODE HOUGH TRANSFORM - Fonda Fernandi Hamid; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
In the field of medical, almost everyone uses computers in their work. Computers can be used as a tool in diagnosing diseases, research, development of drugs, analyzing organs and many of it. This paper presents an approach for white blood cell detection with hough transform. The purpose and objectives of this paper is to make a program that can detect a white blood cell in unstained blood and simplify the detection process to be faster and more accurate than the old way. This paper is proposed with the hope that it can be developed in the future. The results obtained from 2 data sets. The first data set is a collection of images that have white blood cells with an average success rate around 42% and the second data set is a collection of images that do not have white blood cells with an average success rate around 26%.